Banana Xanthomonas wilt infection: the role of debudding and roguing as control options within a mixed cultivar plantation - Nakakawa, J.; Mugisha, J.Y.T.; Shaw, M.W.; Tinzaara, William; Karamura, E.B. (Hindawi Limited, 2017)
An optimal control framework is designed inwhich the use of clean plantingmaterials, debudding, disinfection of tools, and roguing are considered as control measures of Banana Xanthomonas Wilt (BXW) within a plantation of multiple cultivars. A model for a special case of two cultivars (AAA- and ABB-genome cultivars) was analyzed. By Pontryagin’sMaximumPrinciple, we characterized and discussed possible control strategies that substantially reduce the infection levels of BXW within a plantation of ABB- and AAA-genome cultivars. A combination of both prevention and containment controls yielded the greatest decline in the infection levels in both cultivars. Additionally, for effective BXW management, it is important to assess the endemic level of the plantation before application of controls, and once implemented, this should bemaintained even when the disease is undetectable to eliminate possible resurgence